Peran Literasi Keuangan Nelayan Dan Perilaku Rumah Tangga Serta Implikasinya Terhadap Ketahanan Ekonomi Keluarga (Studi Pada Keluarga Nelayan Di Pelabuhan Sadeng, Gunungkidul, Yogyakarta) - Prasetya, Bangun Putra (Jurnal Ketahanan Nasional, 2024)
ABSTRACT The southern coastal area was a priority area to be developed, especially in Sadeng Beach in becoming a fishing port, it was expected to be a mainstay in the economic development of the South Coast area of Gunungkidul Regency and be able to provided welfare to the community, especially fishermen. Welfare was influenced by a number of factors including the limited quality of human resources in understanding financial literacy. Good financial knowledge or Financial Literacy was needed so that financial management could be better by placing money in accordance with appropriate goods, so that it could be an effort to controled household consumptive behavior in achieving family economic resilience. This study aimed to determined the role of household behavior in mediating the influence of financial literacy in achieving family economic resilience. The study used an explanatory approach. This research was included in the category of quantitative research because it involved numerical data, measured objective facts, focused on variables, and involved statistical analysis. Hypothesis testing using Smart PLS. The results showed that with the role of good financial literacy applied in everyday life, it would have an impact on financial resilience. In addition, if a person's literacy ability was able to be applied and was able to controled household behavior in controlling finances and saving, it would have a good impact on family economic resilience